Book review: Why love matters: How affection shapes a baby’s brain. Sue Gerhardt. London, Routledge, 2008. 256pp, ISBN 9781583918173 - Irene Stevens (Scottish Journal of Residential Child Care)
I found out about this book from a good friend who was pregnant. When I heard the name of the book, I thought 'Oh yes….cuddly self-help book for mums-to-be' and dismissed it without another thought. I was, however, encouraged to return to it after hearing Professor David Howe speak about the biological basis of attachment at the SIRCC national conference in Crieff this year….. and I am so glad that I did.